2020
DOI: 10.1038/s41598-020-75125-2
|View full text |Cite
|
Sign up to set email alerts
|

Transport of ultrasmall gold nanoparticles (2 nm) across the blood–brain barrier in a six-cell brain spheroid model

Abstract: The blood–brain barrier (BBB) is an efficient barrier for molecules and drugs. Multicellular 3D spheroids display reproducible BBB features and functions. The spheroids used here were composed of six brain cell types: Astrocytes, pericytes, endothelial cells, microglia cells, oligodendrocytes, and neurons. They form an in vitro BBB that regulates the transport of compounds into the spheroid. The penetration of fluorescent ultrasmall gold nanoparticles (core diameter 2 nm; hydrodynamic diameter 3–4 nm) across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 54 publications
3
89
0
Order By: Relevance
“…More complex in vivo systems can also be reproduced in a spheroid model, such as a blood-brain barrier made up multiple cell types in a multicellular spheroid. This was explored by Sokolova et al that showed that ultrasmall GNPs can cross this barrier, illustrating the useful nature of the 3D spheroid [ 46 ]. Ultrasmall GNPs have previously been explored in a 3D tumor spheroid model, demonstrating that smaller 2 nm and 6 nm GNPs can penetrate deeper into the tissue when compared to that of 15 nm GNPs [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…More complex in vivo systems can also be reproduced in a spheroid model, such as a blood-brain barrier made up multiple cell types in a multicellular spheroid. This was explored by Sokolova et al that showed that ultrasmall GNPs can cross this barrier, illustrating the useful nature of the 3D spheroid [ 46 ]. Ultrasmall GNPs have previously been explored in a 3D tumor spheroid model, demonstrating that smaller 2 nm and 6 nm GNPs can penetrate deeper into the tissue when compared to that of 15 nm GNPs [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the blood–brain barrier permeability of CB839 is challenging, as described in several in vitro studies [ 19 , 54 ], its specificity to inhibit GLS1 and the connection between response and IDH1 DNA mutation status of cancer patients [ 9 ] makes it a promising candidate for precision cancer therapy. Although an increased diffusion through the barrier is expected when attaching the small molecule to Au NPs [ 55 , 56 , 57 ], CB839 could also be part of an intraventrical, intrathecal, or localized intracranial chemotherapy. For intracranial chemotherapy, the BBB problematic could even be avoided because the drug is directly applied to the tumor cavity during tumor resection [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The blood–brain barrier (BBB) is impermeable to most of the conventional drugs whereas nano-drugs can penetrate through it, treating CNS and brain disorders ( Sokolova et al, 2020 ; Kumarasamy and Sosnik, 2021 ). However, NP-induced neurotoxicity needs to be evaluated properly using a suitable toxicity evaluation model.…”
Section: Nanotoxicity Assessment Using the Organoid Modelmentioning
confidence: 99%